Meetings with remarkable men - Gurdjieff, G. (London : Routledge & Kegan Paul, 1963)
Story of Gurdjieff's search through the Middle East and Central Asia for an esoteric brotherhood thought to hold answers to the meaning of life.
"The first English translation by A.R. Orage has been revised and reworked from the Russian for this publication".--P. [vi]. Autobiographical.
Keywords: Gurdjieff, Georges Ivanovitch, -- 1872-1949; History